Jotham and Amon: Two Minor Kings of Judah According to Josephus - Begg, Christopher 1950- (1996)
In the Bible the good king Jotham (see 2 Kgs 15:32–38//2 Chr 27:1–9) and his wicked descendant Amon (see 2 Kgs 21:19–26//2 Chr 33:21–25) are both quite minor figures. This essay explores the treatment of the two kings by Josephus in his Antiquities of the Jews (9:236–43, Jotham; 10.46–48, Amon) in relation to the biblical sources (as represented by MT, LXX and the Targums). From the comparison it emerges that Josephus does not drastically modify the source accounts of Jotham and Amon; also in his version they remain minor kings. On the other hand, his presentation of the royal pair is of interest as exemplifying many of the "rewriting techniques" employed by the historian throughout the biblical segment of the Antiquities.